Crosslinked acrylate polymer and preparation method thereof

By introducing epoxidized urushiol glycidyl ether into acrylate polymers to form a cross-linked structure, the problem of insufficient cohesion under high temperature conditions was solved, realizing the preparation of high-performance acrylate polymers, expanding their application range and responding to the requirements of green and low-carbon development.

CN121108398APending Publication Date: 2025-12-12FUJIAN JIAOFA HI-TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510955117.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-11
Publication Date
2025-12-12

AI Technical Summary

Technical Problem

Existing linear and branched acrylate polymers exhibit insufficient cohesion and significant creep under high temperature conditions or when subjected to high stress, and urushiol glycidyl ether is difficult to disperse uniformly in acrylate systems.

Method used

An epoxidized urushiol glycidyl ether was used as a crosslinking agent to form a crosslinked structure with an acrylate polymer through a ring-opening esterification reaction. The crosslinked acrylate polymer was prepared by combining a specific ratio of monomers and solvents with an initiator and a crosslinking catalyst.

Benefits of technology

The prepared cross-linked acrylate polymer exhibits excellent heat resistance and flexibility, making it suitable for high-temperature environments. It can partially replace petroleum-based chemicals and has good environmental value.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121108398A_ABST
    Figure CN121108398A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of polymerization, and particularly relates to a cross-linked acrylate polymer and a preparation method thereof. A soft monomer (31.4%-37.4%), a hard monomer (1.7%-2.0%), acrylic acid (0.2%-3.0%), an urushiol glycidyl ether crosslinking agent (1.2%-18%) and a mixed solvent (50%-59%) are mixed according to a specific ratio, and a segmented dropwise adding process and a vacuum defoaming curing technology are combined to prepare the adhesive. Compared with the prior art, the cross-linked acrylate polymer has the following advantages: 1, the cross-linked acrylate polymer shows excellent heat resistance and can meet the ever-increasing requirements of the market on high-performance cross-linked acrylate polymers; 2, urushiol glycidyl ether is derived from natural raw lacquer, has functionality and sustainability, and has good environmental protection value; 3, the prepared cross-linked acrylate polymer keeps excellent performance in a high-temperature environment and is suitable for various high-temperature application scenes such as automobile manufacturing, military equipment and electronic materials, and the application range of the acrylic cross-linked acrylate polymer is further expanded.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application belongs to the field of polymerization, and particularly relates to a cross-linked acrylate polymer and a preparation method thereof. BACKGROUND

[0002] Polymeric materials play an indispensable role in modern production and daily life, among which acrylate polymers are favored for their unique combination of properties. These polymers generally exhibit excellent transparency, good weather resistance, and superior adhesion to various substrates, making them widely used in numerous fields such as coatings, adhesives, sealants, and thickeners. By flexibly selecting different types of acrylate monomers for copolymerization, researchers and engineers can precisely control the hardness, glass transition temperature, and other physical and mechanical properties of the resulting polymers to meet the stringent requirements of specific application environments.

[0003] However, linear and branched acrylate polymers may face challenges such as insufficient cohesion, significant creep, and others in certain high-performance applications, such as in high-temperature environments or when required to withstand significant stress or long-term use. To overcome these limitations and significantly improve the overall performance of the material, introducing cross-linking structures has become a key strategy to enhance the comprehensive performance of acrylate polymers.

[0004] In the face of growing global demand for sustainable development and environmental protection, abundant renewable biomass resources are receiving high attention as important raw materials for the production of clean energy and high-value chemicals. This helps to optimize biomass utilization pathways and reduce over-reliance on fossil resources such as coal, oil, and natural gas, thereby alleviating environmental pollution and resource depletion problems. In this context, the design of green cross-linking agents based on natural biomass derivatives has become a research hotspot in recent years. Urushiol, as the main active ingredient of raw lacquer, is a unique natural catechol derivative. Its molecule has both rigid benzene ring and unsaturated long chain structure, which endows it with excellent adhesion, solvent resistance and antioxidant properties. Studies have shown that the catechol hydroxyl group of urushiol can be converted into a highly active glycidyl ether group through epoxidation, providing multiple functional cross-linking sites for the epoxy system. Although urushiol derivatives have been widely used in composite coatings, their research in cross-linked acrylate polymers is still in the exploratory stage.

[0005] As a natural bio-based active molecule, urushiol has a rigid benzene ring structure (which can enhance mechanical properties) and a long alkyl chain (which can improve flexibility). However, its direct application in acrylate systems presents obstacles, such as high viscosity and difficulty in dispersion. The viscosity of urushiol glycidyl ether is >5000 cP (25°C), making it difficult to disperse uniformly in acrylate prepolymers. SUMMARY

[0006] The present application aims to provide a cross-linked acrylate polymer with good heat resistance and comprehensive performance and a preparation method thereof.

[0007] The present application is implemented as follows:

[0008] The cross-linked acrylate polymer of the present application has a structure as shown in

[0009] Formula I:

[0010]

[0011] wherein a, b, c and d are integers, and 2≤a≤3, 8≤b≤20, 12≤c≤25 and 0.1≤d≤4.

[0012] Further, the cross-linked acrylate polymer is made of raw materials including the following weight percentages:

[0013] Soft monomer: 31.4-37.4%

[0014] Hard monomer: 1.7-2.0%

[0015] Acrylic acid: 0.2-3.0%

[0016] Cross-linking agent: 1.2-18%

[0017] Mixed solvent: 50-59%;

[0018] The sum of the above weight percentages is 100%.

[0019] Further, an initiator and a cross-linking catalyst are included.

[0020] The initiator is 0.1-0.5% of the total weight of the hard monomer, the soft monomer and the acrylic acid;

[0021] The cross-linking catalyst is 1% of the weight of the acrylic acid.

[0022] Further, the hard monomer is selected from one or more of methyl acrylate, methyl methacrylate, isopropyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, acrylonitrile and styrene;

[0023] The soft monomer is selected from one or more of butyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate and ethyl acrylate;

[0024] The mixed solvent is composed of ethyl acetate and xylene in a weight ratio of 3:1;

[0025] The cross-linking agent is an epoxidized modified urushiol glycidyl ether.

[0026] Further, the crosslinking catalyst is 1,5,7-triazabicyclo[4.4.0]dec-5-ene;

[0027] The initiator is azobisisobutyronitrile and / or dibenzoyl peroxide.

[0028] The preparation method of the crosslinked acrylic ester polymer comprises the following steps:

[0029] (1) Mix the hard monomer, the soft monomer, the acrylic acid and 40-60% of the total solvent, and heat to 80°C under nitrogen protection;

[0030] (2) Mix the remaining monomer, 20-30% of the total solvent and 45-55% of the initiator, and drop into the reaction system at a constant speed, and react for 1 hour after dropping;

[0031] (3) Mix the remaining initiator and the remaining solvent, drop, and react for 3 hours after dropping, to obtain the acrylic ester copolymer;

[0032] (4) Add the crosslinking agent and the crosslinking catalyst to the copolymer and stir uniformly;

[0033] (5) Preheat the polytetrafluoroethylene mold, inject the mixed liquid, and vacuum degassing until no bubbles are generated;

[0034] (6) Curing at 120°C for 10 minutes, cooling to room temperature and demolding.

[0035] The present application has the following advantages:

[0036] 1. The crosslinked acrylic ester polymer provided by the present application exhibits excellent heat resistance, and can meet the increasing demand of the market for high-performance crosslinked acrylic ester polymers;

[0037] 2. The urushiol glycidyl ether is derived from natural raw lacquer, has functionality and sustainability, partially replaces petroleum-based chemicals, responds to the requirements of green and low-carbon development, and has good environmental protection value;

[0038] 3. The crosslinked acrylic ester polymer prepared by the present application maintains excellent performance in high-temperature environment, is suitable for various high-temperature application scenarios such as automobile manufacturing, military equipment and electronic materials, and further expands the use range of acrylic crosslinked acrylic ester polymers. BRIEF DESCRIPTION OF DRAWINGS

[0039] The present application will be further described below with reference to the accompanying drawings and examples.

[0040] Figure 1 It is the Fourier transform infrared spectrum detection atlas of urushiol glycidyl ether.

[0041] Figure 2The Fourier transform infrared spectroscopy detection pattern of the crosslinked acrylate polymer.

[0042] Figure 3 The TG pattern of the crosslinked acrylate polymer prepared in the embodiment.

[0043] Figure 4 The rheological pattern of the crosslinked acrylate polymer prepared in the embodiment. DETAILED DESCRIPTION

[0044] Although the specific embodiments of the present application are described above, it should be understood by those skilled in the art that the specific embodiments described are only illustrative, and are not intended to limit the scope of the present application, and equivalent modifications and variations made by those skilled in the art in accordance with the spirit of the present application should be covered within the scope of the claims of the present application.

[0045] The preparation method of the crosslinked acrylate polymer of the present application comprises the following steps:

[0046] (1) using acrylic acid, butyl acrylate, isooctyl acrylate and methyl methacrylate as monomers, preparing a linear acrylate polymer by free radical polymerization;

[0047]

[0048] (2) performing ring-opening esterification reaction between the epoxy group of the urushiol glycidyl ether and the carboxyl group of the acrylic acid, to obtain the crosslinked acrylate polymer. Figure 2 )。

[0049]

[0050] The prepared crosslinked acrylate polymer material exhibits good thermal stability, and the initial thermal decomposition temperature is higher than 200 degrees Celsius ( Figure 3 ).

[0051] The crosslinked acrylate polymer material exhibits good flexibility, and in the room temperature rheological test, the material exhibits high chain segment movement ability and energy dissipation ability under low speed and high speed deformation ( Figure 4 ).

[0052] The preparation method of the urushiol glycidyl ether in the present application is as follows:

[0053] (1) In a 250 mL four-necked flask equipped with a thermometer, a mechanical stirrer, a condenser and a constant pressure dropping funnel, add epichlorohydrin 38 g, tetrabutylammonium bromide 1 g and crude urushiol 13 g in sequence, heat the reaction system to 60 °C, and react for 3 hours under stirring, then slowly drop 16 g of 20% mass fraction sodium hydroxide aqueous solution into the reaction system by using a constant pressure dropping funnel, and maintain stirring at 60 °C for 2 hours after the dropping is completed, then cool to room temperature, extract the reaction product with ethyl acetate, wash the obtained organic phase with saturated brine, dry with anhydrous sodium sulfate, and concentrate under reduced pressure at 65 °C to obtain.

[0054] (2) After the reaction is completed, extract the reaction product with ethyl acetate, wash the obtained organic phase with saturated brine, dry with anhydrous sodium sulfate, and finally concentrate under reduced pressure at 65 °C to remove excess epichlorohydrin and ethyl acetate to obtain the urushiol glycidyl ether product. Figure 1

[0055] The raw materials and catalysts used in the embodiments of the present application are all commercially available products; all tests are carried out according to conventional test methods, and the parameter settings of the test instruments are all carried out according to the recommended conditions of the equipment manufacturers.

[0056] Example 1

[0057] (1) Mix methyl methacrylate 1 g, butyl acrylate 9 g, isooctyl acrylate 10 g, acrylic acid 0.125 g, ethyl acetate 7.5 g and xylene 2.5 g, and then add them into a four-necked flask equipped with a stirrer, a constant pressure dropping funnel, a thermometer and a condenser, and then raise the reaction temperature to 80 °C under a nitrogen atmosphere, uniformly stir dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g and xylene 2.5 g, and then drop them into the reaction container through the constant pressure dropping funnel, and start timing the reaction for 1 h.

[0058] (2) After the reaction, uniformly stir the remaining dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g and xylene 2.5 g, and then drop them into the reaction container through the constant pressure dropping funnel, and then maintain constant temperature reaction for 3 hours under a nitrogen atmosphere after the dropping is completed, and then cool to room temperature.

[0059] (3) Add 1,5,7-triazabicyclo[4.4.0]dec-5-ene 0.01 g and urushiol glycidyl ether 0.75 g into the glue solution, and continue to stir until uniform, preheat the polytetrafluoroethylene mold, quickly pour the mixed liquid into the mold, place it in a vacuum oven, vacuum degas until the bubbles completely disappear, take out the mold after 10 min of curing at 120 °C, and then cool to room temperature and demold. Thus, a crosslinked acrylate polymer is obtained, that is, a in formula I is 2, b is 11, c is 14, and d is 0.3.

[0060] Example 2​

[0061] (1) After mixing methyl methacrylate 1 g, butyl acrylate 9 g, isooctyl acrylate 10 g, acrylic acid 0.25 g, ethyl acetate 7.5 g and xylene 2.5 g, they were added to a four-necked flask equipped with a stirring device, a constant pressure dropping funnel, a thermometer and a condenser. The reaction temperature was raised to 80°C under a nitrogen atmosphere, and dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g and xylene 2.5 g were stirred uniformly and dropped uniformly into the reaction vessel through the constant pressure dropping funnel, and the reaction was timed for 1 h.

[0062] (2) After the reaction, the remaining dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g and xylene 2.5 g were stirred uniformly and dropped uniformly into the reaction vessel through the constant pressure dropping funnel, and after the dropping was completed, the reaction was carried out at a constant temperature for 3 h under a nitrogen atmosphere, and then cooled to room temperature.

[0063] (3) 1,5,7-triazabicyclo[4.4.0]dec-5-ene 0.02 g and urushiol glycidyl ether 1.51 g were added to the glue solution, and stirring was continued until uniformity. A polytetrafluoroethylene mold was preheated, and the mixed liquid was quickly poured into the mold. The mold was placed in a vacuum oven, and vacuum degassing was carried out until the bubbles completely disappeared. After 10 min of curing at 120°C, the mold was removed and cooled to room temperature. The crosslinked acrylate polymer was obtained, i.e., a = 2, b = 11, c = 14, and d = 0.6 in Formula I.

[0064] Example 3

[0065] (1) After mixing methyl methacrylate 1 g, butyl acrylate 9 g, isooctyl acrylate 10 g, acrylic acid 0.5 g, ethyl acetate 7.5 g and xylene 2.5 g, they were added to a four-necked flask equipped with a stirring device, a constant pressure dropping funnel, a thermometer and a condenser. The reaction temperature was raised to 80°C under a nitrogen atmosphere, and dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g and xylene 2.5 g were stirred uniformly and dropped uniformly into the reaction vessel through the constant pressure dropping funnel, and the reaction was timed for 1 h.

[0066] (2) After the reaction, the remaining dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g and xylene 2.5 g were stirred uniformly and dropped uniformly into the reaction vessel through the constant pressure dropping funnel, and after the dropping was completed, the reaction was carried out at a constant temperature for 3 h under a nitrogen atmosphere, and then cooled to room temperature.

[0067] (3) To the glue solution, 1, 5, 7-triazabicyclo [4.4.0] dec-5-ene 0.04 g and urushiol glycidyl ether 3.02 g were added, and stirring was continued until uniform. The polytetrafluoroethylene mold was preheated, and the mixed liquid was quickly poured into the mold. The mold was placed in a vacuum oven, and vacuum degassing was performed until the bubbles completely disappeared. After 10 min of curing at 120°C, the mold was removed and cooled to room temperature, and then demolded. Thus, a crosslinked acrylic ester polymer was obtained, i.e., in formula I, a is 2, b is 11, c is 14, and d is 1.

[0068] Example 4

[0069] (1) Methyl methacrylate 1 g, butyl acrylate 9 g, isooctyl acrylate 10 g, acrylic acid 0.75 g, ethyl acetate 7.5 g, and xylene 2.5 g were mixed and added to a four-necked flask equipped with a stirring device, a constant-pressure dropping funnel, a thermometer, and a condenser tube. The reaction temperature was raised to 80°C under a nitrogen atmosphere, and dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g, and xylene 2.5 g were stirred uniformly and dropped uniformly into the reaction vessel through the constant-pressure dropping funnel. The reaction was started and timed for 1 h.

[0070] (2) After the reaction, the remaining dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g, and xylene 2.5 g were stirred uniformly and dropped uniformly into the reaction vessel through the constant-pressure dropping funnel. After the dropping was completed, the reaction was performed for 3 h under a constant temperature in a nitrogen atmosphere, and then the reaction was cooled to room temperature.

[0071] (3) To the glue solution, 1, 5, 7-triazabicyclo [4.4.0] dec-5-ene 0.06 g and urushiol glycidyl ether 4.53 g were added, and stirring was continued until uniform. The polytetrafluoroethylene mold was preheated, and the mixed liquid was quickly poured into the mold. The mold was placed in a vacuum oven, and vacuum degassing was performed until the bubbles completely disappeared. After 10 min of curing at 120°C, the mold was removed and cooled to room temperature, and then demolded. Thus, a crosslinked acrylic ester polymer was obtained, i.e., in formula I, a is 2, b is 11, c is 14, and d is 2.

[0072] Example 5

[0073] (1) Methyl methacrylate 1 g, butyl acrylate 9 g, isooctyl acrylate 10 g, acrylic acid 1 g, ethyl acetate 7.5 g, and xylene 2.5 g were mixed and added to a four-necked flask equipped with a stirring device, a constant-pressure dropping funnel, a thermometer, and a condenser tube. The reaction temperature was raised to 80°C under a nitrogen atmosphere, and dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g, and xylene 2.5 g were stirred uniformly and dropped uniformly into the reaction vessel through the constant-pressure dropping funnel. The reaction was started and timed for 1 h.

[0074] (2) After the reaction, the remaining dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g and xylene 2.5 g were stirred uniformly and added uniformly to the reaction vessel through a constant pressure separatory funnel. After the addition was completed, the reaction was carried out at a constant temperature for 3 hours in a nitrogen atmosphere, and then cooled to room temperature.

[0075] (3) 1,5,7-triazabicyclo[4.4.0]dec-5-ene 0.08 g and urushiol glycidyl ether 6.04 g were added to the glue solution, and stirring was continued until uniform. The polytetrafluoroethylene mold was preheated, the mixed liquid was quickly poured into the mold, and the mold was placed in a vacuum oven. Vacuum degassing was carried out until the bubbles completely disappeared. After 10 min of curing at 120°C, the mold was removed and cooled to room temperature, and then demolded. The crosslinked acrylate polymer was obtained, i.e., in formula I, a is 2, b is 11, c is 14, and d is 3.

[0076] Example 6

[0077] (1) Methyl methacrylate 1 g, butyl acrylate 9 g, isooctyl acrylate 10 g, acrylic acid 1.5 g, ethyl acetate 7.5 g and xylene 2.5 g were mixed and then added to a four-necked flask equipped with a stirring device, a constant pressure separatory funnel, a thermometer and a condenser. The reaction temperature was raised to 80°C under a nitrogen atmosphere, and dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g and xylene 2.5 g were stirred uniformly and added uniformly to the reaction vessel through a constant pressure separatory funnel. The reaction was started and carried out for 1 h.

[0078] (2) After the reaction, the remaining dibenzoyl peroxide 0.01 g, ethyl acetate 7.5 g and xylene 2.5 g were stirred uniformly and added uniformly to the reaction vessel through a constant pressure separatory funnel. After the addition was completed, the reaction was carried out at a constant temperature for 3 hours in a nitrogen atmosphere, and then cooled to room temperature.

[0079] (3) 1,5,7-triazabicyclo[4.4.0]dec-5-ene 0.12 g and urushiol glycidyl ether 9.06 g were added to the glue solution, and stirring was continued until uniform. The polytetrafluoroethylene mold was preheated, the mixed liquid was quickly poured into the mold, and the mold was placed in a vacuum oven. Vacuum degassing was carried out until the bubbles completely disappeared. After 10 min of curing at 120°C, the mold was removed and cooled to room temperature, and then demolded. The crosslinked acrylate polymer was obtained, i.e., in formula I, a is 2, b is 11, c is 14, and d is 4.

[0080] The analysis method in the examples of the present application is as follows:

[0081] Infrared spectroscopy analysis was performed using a Nicolet iS50 infrared spectrometer with a wavelength range of 4000-500 cm -1 , and a spectral resolution of 4 cm -1 .

[0082] Thermogravimetric analysis was performed using a TG 209 F3 thermogravimetric analyzer under nitrogen atmosphere, the test temperature was raised from 30 °C to 600 °C at a rate of 10 °C / min.

[0083] Rheological properties were tested using a HAAKE™ MARS™ rotational rheometer, sweeping the frequency in the range 0.628 - 400 rad s -1 of the PSA at 0.1% strain amplitude at 24 °C.

Claims

1. A crosslinked acrylate polymer, characterized in that: The structure of the cross-linked acrylate polymer is shown in Formula I: Where a, b, c, and d are integers, the range of a is 2≤a≤3, the range of b is 8≤b≤20, the range of c is 12≤c≤25, and the range of d is 0.1≤d≤4.

2. The crosslinked acrylate polymer according to claim 1, characterized in that: Made from raw materials comprising the following weight percentages: Soft monomers: 31.4%–37.4% Hard monomers: 1.7–2.0% Acrylic acid: 0.2–3.0% Urushiol glycidyl ether crosslinking agent: 1.2%–18% Mixed solvent: 50-59%; The total weight percentage above is 100%.

3. The crosslinked acrylate polymer according to claim 2, characterized in that: It also includes initiators and crosslinking catalysts; The initiator is 0.1-0.5% of the total weight of hard monomers, soft monomers, and acrylic acid; The crosslinking catalyst is 1% of the weight of acrylic acid.

4. The crosslinked acrylate polymer according to claim 3, characterized in that: The hard monomer is selected from one or more of the following: methyl acrylate, methyl methacrylate, isopropyl methacrylate, 2-hydroxypropyl methacrylate, vinyl acetate, acrylonitrile, and styrene; The soft monomer is selected from one or more of the following: butyl acrylate, isooctyl acrylate, 2-ethylhexyl acrylate, and ethyl acrylate; The mixed solvent is composed of ethyl acetate and xylene in a weight ratio of 3:1; The crosslinking agent is epoxidized urushiol glycidyl ether.

5. The crosslinked acrylate polymer according to claim 3, characterized in that: The crosslinking catalyst is 1,5,7-triazabicyclo[4.4.0]dec-5-ene; The initiator is azobisisobutyronitrile and / or benzoyl peroxide.

6. A method for preparing the crosslinked acrylate polymer according to any one of claims 1 to 5, characterized in that: Includes the following steps: (1) Mix hard monomers, soft monomers, acrylic acid and 40-60% total solvent, and heat to 80°C under nitrogen protection; (2) Mix the remaining monomer, 20-30% of the total solvent and 45-55% of the initiator, and add them dropwise to the reaction system at a uniform rate. After the addition is complete, keep the temperature constant for 1 hour. (3) The remaining initiator and the remaining solvent were mixed and added dropwise. After the addition was completed, the mixture was kept at a constant temperature for 3 hours to obtain the acrylate copolymer. (4) Add crosslinking agent and crosslinking catalyst to the copolymer and stir until homogeneous; (5) Preheat the polytetrafluoroethylene mold, inject the mixture, and degas under vacuum until there are no bubbles; (6) Curing at 120℃ for 10 minutes, then cooling to room temperature for demolding.